Compliance Audit Sebagai Alat Untuk Mendorong Tercapainya Tujuan Organisasi (Studi kasus pada Hotel The 101 Suryakencana Bogor) - Khairunnisa, Nova; Yuliandi, Yuliandi (Institut Bisnis dan Informatika Kesatuan, 2019)
The purpose of this study was to determine the implementation of compliance audit at The 101 Suryakancana Bogor Hotel, knowing the achievement of Bogor 101 The Hotel Suryakancana through a predetermined procedural policy, and knowing whether compliance audit is influential in achieving the 101 The Suryakancana Bogor Hotel goal. The method used in this study is a qualitative descriptive method. This method aims to understand the phenomena that occur based on existing theories compared to practice when conducting research in the field. The author explains the implementation of compliance audit, achievement of organizational objectives, and compliance audit as a tool to achieve organizational goals. The results showed that the implementation of compliance audit at The 1O1 Suryakencana Hotel Bogor was conducted through five stages: audit planning, audit testing and evaluation, reporting of audit findings, recommendations and monitoring and follow-up. Audit Compliance at The 1O1 Suryakencana Bogor Hotel can be said to be